(untitled) (Journal of Universal Science Research, 2024)
This article is a study on the implementation of the active contours method using mathematical descriptions to identify objects in the work area of a mobile robot. The program, developed in Python in the PyCharm 2022.2.3 (Professional Edition) environment, is based on the principles of the active contour method, ensuring accurate selection of objects in images. Experiments conducted on matchbox contour extraction with the help of ESP32-Cam module confirm the effectiveness of the method in real-world conditions, demonstrating its potential for application in various fields of mobile robotics and computer vision.